2023
DOI: 10.1002/smll.202207961
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring a Minimal Self‐Replicate DNA Circuit for Highly Efficient Intracellular Imaging of microRNA

Abstract: Trace analyte detection in complex intracellular environment requires the development of simple yet robust self‐sufficient molecular circuits with high signal‐gain and anti‐interference features. Herein, a minimal non‐enzymatic self‐replicate DNA circuitry (SDC) system is proposed with high‐signal‐gain for highly efficient biosensing in living cells. It is facilely engineered through the self‐stacking of only one elementary cascade hybridization reaction (CHR), thus is encoding with more economic yet effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Additionally, Wang group have developed a variety of amplification strategies for specific and sensitive imaging of small molecules, 85 enzymes, 86 and miRNAs [87][88][89][90][91][92][93][94][95][96] in the intracellular environment. For example, several research studies have demonstrated that ATP is a potential cancer biomarker.…”
Section: Molecule Sensing and Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Wang group have developed a variety of amplification strategies for specific and sensitive imaging of small molecules, 85 enzymes, 86 and miRNAs [87][88][89][90][91][92][93][94][95][96] in the intracellular environment. For example, several research studies have demonstrated that ATP is a potential cancer biomarker.…”
Section: Molecule Sensing and Imagingmentioning
confidence: 99%
“…Compared to complicated conventional designs of reported isothermal autocatalytic DNA circuits for biosensing, they developed simpler strategies of self-amplification. For instance, they constructed a self-replicate DNA circuits (SDC) system, 90 which contains merely one CHR element for generating amplified signals. In this SDC process, trigger ( T ) could activate the assembly of CHR carrying numerous new reconstituted T for continuously motivating the CHR system, resulting in the generation of hyperbranched dsDNA products with exponential signal amplification (Fig.…”
Section: Application In Intracellular Environmentmentioning
confidence: 99%
“…These enzyme-free DNA circuits include hybridization chain reaction (HCR), [9] catalytic hairpin assembly (CHA), [8] entropy-driven reaction (EDR), [37] and cyclic cleavage reaction (DNAzyme). [38] Additionally, the abundant types of cascaded [39][40][41][42][43][44] or autocatalytic DNA circuits [45][46][47][48][49][50][51][52][53][54] have been rationally engineered for amplified bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their ease of synthesis, flexible programmability, and high biocompatibility, the genetic material DNA-based probes have become powerful tools for rationally designing molecular machines with nanoscale dimensions in biosensing. , These DNA-based probes can execute robotic tasks in response to specific molecular inputs and transduce them into readable signal outputs to engineer dynamic and intricate functions without human intervention. , Typically, the DNA probes have been successfully used to detect and image specific molecules such as ribonucleic acid, metal ions, and small molecules, as well as changes in the cellular environment such as temperature and pH . Furthermore, a wealth of nucleic acid molecular probes, including small interfering RNA (siRNA) and antisense single-stranded DNA oligonucleotides (ASO), are devoted to gene interference therapy in clinical practice. , However, since the naked DNAs are unable to penetrate cell membranes and are prone to rapid degradation, the application of DNA probes often requires the use of various nanomaterials as vectors for real-time imaging of specific tumor biomarkers and addressing their low therapeutic performance as drug delivery systems. , …”
Section: Introductionmentioning
confidence: 99%